PENGARUH SISTEM KEUANGAN DESA TERHADAP AKUNTABILITAS DENGAN PENGELOLAAN KEUANGAN DESA SEBAGAI VARIABEL INTERVENING - Harafonna, Cut Nadhifa; Indriani, Mirna (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2019)
This study aims to examine the effect of the village financial systems on accountability and the role of village financial management as an intervening variable on the relationship of village financial systems to accountability. The population in this study were villages in Pidie Jaya which consisted of 222 villages in 8 sub-districts. Sampling is done using proportional random sampling techniques. The respondents of the study were 102 people from 34 selected villages consisting of village heads, secretaries and treasurers. Data collection is done using a questionnaires that is delivered directly to the respondent. data processing is done by PLS SEM (Structural Equation Modeling-Partial Least Square). The results of this study indicate that village financial systems influence accountability. financial management cannot be an intervening variable for the relationship of the village financial system with accountability.